Characterization of recombination intermediates from DNA injected into Xenopus laevis oocytes: evidence for a nonconservative mechanism of homologous recombination. - Maryon, E (1991)
Homologous recombination between DNA molecules injected into Xenopus laevis oocyte nuclei is extremely efficient if injected molecules have overlapping homologous ends. Earlier work demonstrated that ends of linear molecules are degraded by a 5'----3' exonuclease activity, yielding 3' tails that participate in recombination. Here, we have characterized intermediates further advanced along the recombination pathway. The intermediates were identified by their unique electrophoretic and kinetic properties. Two-dimensional gel electrophoresis and hybridization with oligonucleotide probes showed that the intermediates had heteroduplex junctions within their homologous overlaps in which strands ending 3' were full length and those ending 5' were shortened. Additional characterization suggested that these intermediates had formed by the annealing of complementary 3' tails. Annealed junctions made in vitro were rapidly processed to products, indicating that they are on the normal recombination pathway. These results support a nonconservative, single-strand annealing mode of recombination. This recombination mechanism appears to be shared by many organisms, including bacteria, fungi, plants, and mammals.